Use of sonography to evaluate carotid atherosclerosis in the elderly. The Cardiovascular Health Study. CHS Collaborative Research Group. - O'Leary, D H; Polak, J F; Wolfson, S K; Bond, M G; Bommer, W; Sheth, S; Psaty, B M; Sharrett, A R; Manolio, T A (Stroke, 1991)
Carotid sonography is being performed on more than 5,000 participants in the Cardiovascular Health Study, a prospective, multicenter study of cardiovascular disease in men and women aged 65 years and older. The sonographic methods used to examine and measure the extracranial carotid arteries are described. Initial validation studies were performed on 61 subjects with a mean age of 68.6 years. Analysis of within- and between-sonographer differences and between-reader differences were performed for selected variables. In general, the mean absolute differences for within- and between-sonographer comparisons were small, with even less variability between readers. Variability was less for the common carotid artery than for the internal carotid artery. These data suggest that carotid sonography is a reliable and reproducible method for use in the study of carotid atherosclerosis in population studies.
Keywords: Age Factors; Aged; Arteriosclerosis; Carotid Arteries; Carotid Artery Diseases; Carotid Artery, Internal; Female; Humans; Image Interpretation, Computer-Assisted; Image Processing, Computer-Assisted; Male; Prospective Studies; Ultrasonography

Distribution and correlates of sonographically detected carotid artery disease in the Cardiovascular Health Study. The CHS Collaborative Research Group. - O'Leary, D H; Polak, J F; Kronmal, R A; Kittner, S J; Bond, M G; Wolfson, S K; Bommer, W; Price, T R; Gardin, J M; Savage, P J (Stroke, 1992)
BACKGROUND AND PURPOSE: This article describes the prevalence of extracranial carotid atherosclerosis assessed by ultrasonography, its association with risk factors, and its relation to symptomatic coronary disease and stroke in men and women aged > or = 65 years. METHODS: Maximum percent stenosis, maximum common carotid artery wall thickness, and maximum internal carotid artery wall thickness were assessed using duplex ultrasound in 5,201 men and women aged > or = 65 years in the Cardiovascular Health Study, a study of the risk factors and natural history of cardiovascular disease in the elderly. Existing coronary disease and stroke were assessed by physical examination and participant history. RESULTS: Detectable carotid stenosis was present in 75% of men and 62% of women, although the prevalence of > or = 50% stenosis was low, 7% in men and 5% in women. Maximum stenosis and maximum wall thickness measurements increased with age and were uniformly greater at all ages in men than in women (p < 0.00001). Established risk factors for atherosclerosis (hypertension, smoking, diabetes) and indications of vascular disease (left ventricular hypertrophy, major electrocardiographic abnormality, bruits, and history of heart disease or stroke) related to all three carotid artery measures in the elderly. Of the three ultrasound measures, the best correlate for a history of coronary disease was maximum internal carotid artery wall thickness. For stroke the best correlate was common carotid artery wall thickness. Multiple logistic regression models of prevalent coronary heart disease and stroke that included the ultrasound findings indicated, after adjustment for age and sex, that maximum internal wall thickness and maximum common carotid wall thickness were significant correlates of both. Maximum stenosis did not add significantly to the correlation. CONCLUSIONS: In the elderly the incidence of carotid atherosclerosis was high, although the frequency of severe disease was low. The prevalence and severity of carotid atherosclerosis continued to increase with age even in the late decades of life, and more disease was found in men than in women at all ages. Known risk factors for atherosclerosis continued to relate to carotid abnormalities in the later decades of life, both in symptomatic and asymptomatic subjects.
Keywords: Aged; Arteriosclerosis; Cardiomegaly; Carotid Artery Diseases; Cerebrovascular Disorders; Coronary Disease; Female; Humans; Male; Medical Records; Prevalence; Regression Analysis; Risk Factors; Ultrasonography

The distribution of coagulation factors VII and VIII and fibrinogen in adults over 65 years. Results from the Cardiovascular Health Study. - Tracy, R P; Bovill, E G; Fried, L P; Heiss, G; Lee, M H; Polak, J F; Psaty, B M; Savage, P J (Ann Epidemiol, 1992)
The Cardiovascular Health Study (CHS) was designed to examine cardiovascular disease and its risk factors in older adults. We report here the distributions of the coagulation factors fibrinogen, factor VII, and factor VIII in a population-based cohort of men and women 65 years or older. In other studies of middle-aged individuals, these factors were shown to be associated with cardiovascular risk. In the CHS cohort, all three factors were elevated, compared to levels reported in middle-aged individuals, and fibrinogen and factor VIII values were higher in each successive age group; factor VII values, in contrast, declined slightly with age in the CHS cohort. Compared to white subjects, blacks had higher values for fibrinogen and factor VIII and lower values for factor VII. While women had markedly higher values for factor VII and factor VIII than men at all ages in the CHS, mean fibrinogen values were not different between men and women.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Cardiovascular Diseases; Cohort Studies; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Male; Middle Aged; Risk Factors

Age-related trends in cardiovascular morbidity and physical functioning in the elderly: the Cardiovascular Health Study. - Bild, D E; Fitzpatrick, A; Fried, L P; Wong, N D; Haan, M N; Lyles, M; Bovill, E; Polak, J F; Schulz, R (J Am Geriatr Soc, 1993)
OBJECTIVE: To describe relationships between age and sub-clinical cardiovascular disease, manifest chronic disease, and physical functioning and limitations among persons aged 65 years and older, with emphasis on the "oldest old," those 85 years and older. DESIGN: Observational population-based study. SETTING: Four U.S. communities: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Pittsburgh, Pennsylvania. PARTICIPANTS: 5,201 men and women aged 65 years and older. MEASUREMENTS: Demographic data; histories of cardiovascular disease (CVD), chronic lung disease, arthritis, diabetes, and hypertension; measures of subclinical disease including arm and ankle blood pressures, internal carotid wall thickness and stenosis, ejection fraction, left ventricular mass, fractional shortening, and diastolic function, electrocardiographic left ventricular hypertrophy and cardiac injury score, forced expiratory flow and volume; functional status including self-reported physical functioning, hearing and sight limitations and health status, and performance-based measures of function. These variables were examined among men and women in three age groups: 65-74 years, 75-84 years, and 85 + years. Subgroups of participants with and without manifest CVD were also examined. MAIN RESULTS: In women, the prevalence of CVD and other chronic conditions increased with age, and the highest rates occurred among those 85 years and older. In men, prevalence rates increased between the two younger groups, but the oldest group had lower than expected rates for coronary heart disease, cerebrovascular disease, hypertension, and chronic lung disease. In contrast, there were strong age-related linear trends in most of the subclinical measures of blood pressure, atherosclerosis and pulmonary function and in virtually all measures of functional status in both gender groups across the age range. There was a particularly marked decline in functional status between the two older age groups. While subclinical disease was greater and functional status was poorer among those with manifest CVD, with few exceptions, age-related trends were not significantly different between the two groups. CONCLUSIONS: Lower than expected prevalence rates of CVD among those aged 85 years and older, particularly among men, in this study of community-dwelling elderly may represent selection bias or a real plateauing in disease prevalence with age. However, subclinical disease appears to increase and functional status to decline across the age range in both men and women regardless of the presence of CVD. The apparent increase in subclinical disease with age indicates potential for CVD prevention after age 65.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Humans; Male; Prevalence; Sex Distribution; Socioeconomic Factors

Sonographic evaluation of carotid artery atherosclerosis in the elderly: relationship of disease severity to stroke and transient ischemic attack. - Polak, J F; O'Leary, D H; Kronmal, R A; Wolfson, S K; Bond, M G; Tracy, R P; Gardin, J M; Kittner, S J; Price, T R; Savage, P J (Radiology, 1993)
Doppler and real-time ultrasound (US) were performed to evaluate the extent of atherosclerotic changes in the carotid artery and to assess their relationship to prevalent cerebrovascular disease. Real-time US scans and Doppler measurements of the carotid arteries were analyzed in 5,201 subjects aged 65 years or older. Severity of atherosclerotic lesions was associated with increased frequencies of hyperechoic, irregular, and heterogeneous textured lesions (P < .0001). The severity of internal carotid artery stenosis was associated with thickening of the intima-media layer of the common carotid artery wall (r = .37, P < .0001). A history of stroke and transient ischemic attack (TIA) was more likely when hyperechoic, heterogeneous, and irregular lesions were seen in the carotid artery. Internal carotid artery stenosis correlated better with prevalent stroke and TIA than did sonographic descriptions of plaque texture. However, the prevalence of hyperechoic, heterogeneous, and irregular lesions increased as the degree of internal carotid stenosis increased. On real-time images alone, the average of the internal carotid artery maximal wall thickness is the sonographic measure of atherosclerosis that enables the best prediction of prevalent stroke and TIA.
Keywords: Aged; Arteriosclerosis; Carotid Artery Diseases; Carotid Artery, Internal; Carotid Stenosis; Cerebrovascular Disorders; Female; Humans; Ischemic Attack, Transient; Male; Ultrasonography

Temporal patterns of antihypertensive medication use among elderly patients. The Cardiovascular Health Study. - Psaty, B M; Savage, P J; Tell, G S; Polak, J F; Hirsch, C H; Gardin, J M; McDonald, R H (JAMA, 1993)
OBJECTIVES: To estimate the incidence of newly treated hypertension and to describe the patterns of antihypertensive medication use among those aged 65 years and older. DESIGN: Medicare eligibility lists from four US communities (Forsyth County, North Carolina; Washington County, Maryland; Sacramento County, California; and Pittsburgh, Pa) were used to obtain a representative sample of 5201 community-dwelling elderly for the Cardiovascular Health Study, a prospective cohort study of risk factors for coronary heart disease and stroke. Participants were examined at baseline and again 1 year later. The two examinations included standardized questionnaires, blood pressure measurements, and the assessment of medication use by medication inventory. In this cohort analysis, we excluded 231 subjects (4.4%) who did not return for follow-up, 69 (1.3%) who had missing data for medications, and another 495 (9.5%) who were taking "antihypertensive" medications for an indication other than high blood pressure. INTERVENTIONS: None. RESULTS: Among the 4406 participants, 1613 used antihypertensive medications at both visits. Between the two visits, 144 started and 115 stopped antihypertensive therapy. Among nonusers at baseline, the annual incidence of newly treated hypertension was 5.2% in women and 5.6% in men. Due to the number of participants who stopped therapy, the overall prevalence of antihypertensive treatment increased only slightly, from 40.7% to 41.1% in women and from 37.1% to 38.2% in men, during 1 year of follow-up. After adjustment for age, systolic blood pressure, number of antihypertensive drugs, diabetes, and cardiovascular disease, the newly treated hypertensives were about half as likely as the previously treated hypertensives to receive diuretics (odds ratio [OR], 0.59; P = .008) or beta-blockers (OR, 0.52; P = .01); and they were about twice as likely to receive calcium channel blockers (OR, 1.88; P < .004) or angiotensin converting enzyme inhibitors (OR, 2.40; P < .001). A similar pattern of within-person changes over time was apparent among the continuous users. CONCLUSIONS: Between June 1990 and June 1991, physicians were increasingly prescribing angiotensin converting enzyme inhibitors and calcium channel blockers in place of diuretics and beta-blockers for the treatment of hypertension in elderly patients, especially for those just starting therapy.
Keywords: Adrenergic beta-Antagonists; Aged; Analysis of Variance; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Cohort Studies; Diuretics; Drug Utilization; Female; Follow-Up Studies; Humans; Hypertension; Linear Models; Logistic Models; Male; Medicare; Practice Patterns, Physicians'; Recurrence; United States; Vasodilator Agents

Correlates of blood pressure in community-dwelling older adults. The Cardiovascular Health Study. Cardiovascular Health Study (CHS) Collaborative Research Group. - Tell, G S; Rutan, G H; Kronmal, R A; Bild, D E; Polak, J F; Wong, N D; Borhani, N O (Hypertension, 1994)
Although elevated blood pressure is an important predictor of cardiovascular disease and stroke in the elderly, little information exists on the distribution and risk factor correlates of blood pressure in this group. As part of the Cardiovascular Health Study, a population-based cohort study of 5201 men and women aged 65 to 101 years, we investigated correlates of systolic and diastolic blood pressure. Multiple regression analyses were conducted for all participants and a subgroup of 2482 without coronary heart disease and not on antihypertensive therapy (the "healthier" subgroup). In the total group, independent predictors of diastolic blood pressure included heart rate, aortic root dimension, creatinine, hematocrit, alcohol use, and black race (positive associations) and internal carotid artery wall thickness, mitral early/late peak flow velocity, white blood cell count, cigarette smoking, and age (negative associations). Positive predictors of systolic blood pressure included mitral late peak flow velocity, left ventricular mass, common carotid artery wall thickness, serum albumin, factor VII, diabetes, alcohol use, and age; negative predictors were coronary heart disease, uric acid, height, and smoking. In the healthier subgroup, positive predictors of diastolic blood pressure included heart rate, hematocrit, serum albumin, creatinine, and body weight, whereas mitral early/late peak flow velocity, serum potassium, smoking, and age inversely related to diastolic pressure. For the same group, common carotid artery wall thickness, left ventricular mass, serum albumin, factor VII, high-density lipoprotein cholesterol, and age were directly related to systolic blood pressure, whereas serum potassium was inversely related. Both systolic and diastolic pressures varied considerably by geographic site.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Aged; Aged, 80 and over; Aging; Blood Pressure; Cohort Studies; Coronary Disease; Female; Health Surveys; Humans; Hypertrophy, Left Ventricular; Male; Regression Analysis; United States

Predictors of perceived health status in elderly men and women. The Cardiovascular Health Study. - Schulz, R; Mittelmark, M; Kronmal, R; Polak, J F; Hirsch, C H; German, P; Bookwala, J (J Aging Health, 1994)
Baseline data on the perceived health status of participants (N = 5,201) in the Cardiovascular Health Study of the Elderly (CHS) are reported. The authors examined the predictive utility of health-related factors representing eight different domains, assessed gender differences in the prediction of perceived health, and tested a hypothesis regarding the role of known clinical conditions versus subclinical disease in predicting perceived health. Multivariate analyses showed that the majority of the explained variance in self-assessed health is accounted for by variables that fall into four general categories. Although gender differences were small, the analysis showed that the relative importance of several predictor variables did vary by gender.
Keywords: Aged; Cardiovascular Diseases; Data Collection; Female; Forecasting; Geriatric Assessment; Health Status; Humans; Male; Multivariate Analysis; Regression Analysis; Self-Assessment; Sex Factors; United States

Relation of smoking with carotid artery wall thickness and stenosis in older adults. The Cardiovascular Health Study. The Cardiovascular Health Study (CHS) Collaborative Research Group. - Tell, G S; Polak, J F; Ward, B J; Kittner, S J; Savage, P J; Robbins, J (Circulation, 1994)
BACKGROUND: Cigarette smoking has been associated with increased risk of atherosclerotic diseases in hospital-based studies and in studies of middle-aged populations but not in population-based studies of older adults with and without clinical cardiovascular disease. METHODS AND RESULTS: We investigated the relation of smoking to carotid artery atherosclerotic disease, expressed as intimal-medial wall thickness and arterial lumen narrowing (stenosis) measured by ultrasound. Subjects were 5116 older adults participating in the baseline examination of the Cardiovascular Health Study, a community-based study of cardiovascular diseases in older age. With increased smoking there was significantly greater internal and common carotid wall thickening and internal carotid stenosis: current smokers > former smokers > never-smokers; for instance, the unadjusted percent stenosis was 24%, 20%, and 16%, respectively (P < .0001). A significant dose-response relation was seen with pack-years of smoking. These findings persisted after adjusting for other cardiovascular risk factors and were also confirmed when analyses were restricted to those without prevalent cardiovascular disease. The difference in internal carotid wall thickness between current smokers and nonsmokers was greater than the difference associated with 10 years of age among never-smoking participants (0.39 mm versus 0.31 mm). Among all participants, the prevalence of clinically significant (> or = 50%) internal carotid stenosis increased from 4.4% in never-smokers to 7.3% in former smokers to 9.5% in current smokers (P < .0001). CONCLUSIONS: These findings extend previous reports of a positive relation between smoking and carotid artery disease to a population-based sample of older adults using several different indicators of atherosclerotic disease.
Keywords: Aged; Aged, 80 and over; Carotid Arteries; Carotid Stenosis; Cohort Studies; Female; Humans; Male; Smoking; Ultrasonography

Association of fibrinogen and coagulation factors VII and VIII with cardiovascular risk factors in the elderly: the Cardiovascular Health Study. Cardiovascular Health Study Investigators. - Cushman, M; Yanez, D; Psaty, B M; Fried, L P; Heiss, G; Lee, M; Polak, J F; Savage, P J; Tracy, R P (Am J Epidemiol, 1996)
The cross-sectional correlates of three hemostatic factors--fibrinogen, factor VII, and factor VIII--were examined in the Cardiovascular Health Study, a population-based cohort study of 5,201 subjects over age 65 years. Subjects were recruited in 1989-1990 in Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Pittsburgh, Pennsylvania. In multivariate linear regression models, cardiac risk factors significantly associated with fibrinogen were current smoking, race, lipids, and white blood count. In women, alcohol use, obesity, physical activity, and insulin level were also significant, while in men hypertension was correlated. The significant correlates of factor VII were lipids and white blood count in men and estrogen use, alcohol use, race, lipids, insulin level, white blood count, and obesity in women. The independent correlates of factor VIII were insulin, glucose, and race in both sexes; low density lipoprotein cholesterol, white blood count, and diuretic use in men; and alcohol use in women. In multivariate models, factors known to be modifiable risk factors for cardiovascular disease accounted for more of the population variance of these hemostatic factors in women than in men, especially for factor VII. The hemostatic factors may mediate some effects of risk factors on disease, and this should be considered in longitudinal studies.
Keywords: Age Distribution; Aged; Aged, 80 and over; Analysis of Variance; Cardiovascular Diseases; Cohort Studies; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Linear Models; Logistic Models; Male; Prevalence; Risk Factors; Sex Distribution; United States

Carotid artery measures are strongly associated with left ventricular mass in older adults (a report from the Cardiovascular Health Study). - Kronmal, R A; Smith, V E; O'Leary, D H; Polak, J F; Gardin, J M; Manolio, T A (Am J Cardiol, 1996)
Associations of carotid artery diameter and intimal-medial thickness by ultrasound with echocardiographic left ventricular (LV) structure were examined in 3,409 participants in the Cardiovascular Health Study, a population-based study of risk factors for coronary heart disease and stroke in men and women aged > or = 65 years. At baseline, sector-guided M-mode echocardiography and B-mode ultrasound were used to evaluate the left ventricle and carotid arteries, respectively. Common carotid artery diameter and intimal-medial thickness were significantly related to LV mass in correlational analysis (r=0.40 and 0.20, respectively, p<0.01), and each was independently associated with LV mass after adjustment for age, gender, weight, systolic and diastolic blood pressure, antihypertensive medication use, prior coronary heart disease, electrocardiographic abnormalities, high-density lipoprotein, and factor VII. We speculate that changes in the arterial wall affect impedance to LV ejection leading to increases in LV mass. Further follow-up of this cohort is in progress and will help to determine whether such carotid artery measures could, by exacerbating LV hypertrophy, constitute another important risk factor for adverse cardiovascular outcomes.
Keywords: Aged; Carotid Arteries; Cohort Studies; Female; Heart Ventricles; Humans; Hypertrophy, Left Ventricular; Male; Regression Analysis; Risk Factors; Ultrasonography

Compensatory increase in common carotid artery diameter. Relation to blood pressure and artery intima-media thickness in older adults. Cardiovascular Health Study. - Polak, J F; Kronmal, R A; Tell, G S; O'Leary, D H; Savage, P J; Gardin, J M; Rutan, G H; Borhani, N O (Stroke, 1996)
BACKGROUND AND PURPOSE: Common carotid artery (CCA) diameter is thought to increase as a consequence of hypertension and may increase as the thickness of the arterial wall increases. The purpose of this study was to determine CCA dimensions and correlate them with clinical features. METHODS: We performed a cross-sectional, community-based study of adults 65 years of age and older, measuring inner and outer diameter of the CCA in vivo with carotid sonography. Findings were correlated against risk factors for atherosclerosis, CCA intima-media thickness (IMT), and echocardiographically determined left ventricular (LV) mass. RESULTS: Independent variables showing strong positive associations with outer and inner CCA diameter included age, male sex, height, weight, and systolic blood pressure. As an independent variable, LV mass (r = .40 and r = .37, respectively; P < .00001) had a strong positive relation to inner and outer CCA diameters. The relationship between diameter and IMT was different. In a model that controlled for age, sex, and estimated LV mass, an increase of 1 mm in CCA IMT corresponded to a 1.9 mm increase in the outer diameter of the artery (P < .00001) but was not significantly related to the inner diameter (slope = +0.07 mm; P = .26). CONCLUSIONS: Increase in the outer diameter of the CCA is associated with subject size, sex, age, echocardiographically estimated LV mass, and CCA IMT. Increases in internal diameter of the CCA have similar relationships but are not related to IMT. This supports the hypothesis that the human CCA dilates as the thickness of the artery wall increases.
Keywords: Aged; Blood Pressure; Carotid Artery, Common; Cross-Sectional Studies; Echocardiography; Female; Heart Ventricles; Humans; Hypertension; Male; Tunica Intima; Tunica Media

Thickening of the carotid wall. A marker for atherosclerosis in the elderly? Cardiovascular Health Study Collaborative Research Group. - O'Leary, D H; Polak, J F; Kronmal, R A; Savage, P J; Borhani, N O; Kittner, S J; Tracy, R; Gardin, J M; Price, T R; Furberg, C D (Stroke, 1996)
BACKGROUND AND PURPOSE: We investigated the relationships between prevalent coronary heart disease (CHD), clinically manifest atherosclerotic disease (ASD), and major established risk factors for atherosclerosis and intima-media thickness (IMT) in the common carotid arteries (CCA) and internal carotid arteries (ICA) separately and in combination in older adults. We wished to determine whether a noninvasive measurement can serve as an indicator of clinically manifest atherosclerotic disease and to determine which of the two variables, CCA IMT or ICA IMT, is a better correlate. METHODS: IMT of the CCA and ICA was measured with duplex ultrasound in 5117 of 5201 individuals enrolled in the Cardiovascular Health Study, a study of the risk factors and the natural history of cardiovascular disease in adults aged 65 years or more. Histories of CHD, peripheral arterial disease, and cerebrovascular disease were obtained during baseline examination. Risk factors included cholesterol levels, cigarette smoking, elevated blood pressure, diabetes, age, and sex. Relationships between risk factors and IMT were studied by multiple regression analysis and canonical variate analysis. Prediction of prevalent CHD and ASD by IMT measurements in CCAs and ICAs were made by logistic regression, adjusting for age and sex. RESULTS: IMT measurements of the CCAs and ICAs were greater in persons with CHD and ASD than those without, even after controlling for sex (P < .001). IMT measurements in the ICA were greater than those in the CCA. Risk factors for ASD accounted for 17% and 18% of the variability in IMT in the CCA and ICA, respectively. These same risk factors accounted for 25% of the variability of a composite measurement consisting of the sum of the ICA IMT and CCA IMT. The ability to predict CHD and ASD was greater for ICA IMT (odds ratio [confidence interval]: 1.36 [1.31 to 1.41] and 1.35 [1.25 to 1.44], respectively) than for CCA IMT (1.09 [1.05 to 1.13] and 1.17 [1.09 to 1.25]). CONCLUSIONS: Whereas CCA IMT is associated with major risk factors for atherosclerosis and existing CHD and ASD in older adults, this association is not as strong as that for ICA IMT. The combination of these measures relates more strongly to existing CHD and ASD and cerebrovascular disease risk factors than either taken alone.
Keywords: Adult; Aged; Arteriosclerosis; Blood Pressure; Carotid Artery, Common; Carotid Artery, Internal; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; Diabetes Mellitus; Diabetic Angiopathies; Electrocardiography; Female; Humans; Male; Medical History Taking; Physical Examination; Prospective Studies; Regression Analysis; Risk Factors; Sex Characteristics; Smoking; Tunica Intima; Tunica Media; Ultrasonography

Asymptomatic internal carotid artery stenosis defined by ultrasound and the risk of subsequent stroke in the elderly. The Cardiovascular Health Study. - Longstreth, W T; Shemanski, L; Lefkowitz, D; O'Leary, D H; Polak, J F; Wolfson, S K (Stroke, 1998)
BACKGROUND AND PURPOSE: We sought in this study to relate carotid ultrasound findings in asymptomatic older adults to the 5-year risk of various cerebrovascular outcomes used in the Asymptomatic Carotid Atherosclerosis Study (ACAS). METHODS: The Cardiovascular Health Study (CHS) is a longitudinal study of people 65 years and older. Analyses of internal carotid artery stenosis defined by multiple different cutoffs of peak systolic velocity, rather than one particular cutoff, were performed in the 5441 participants who underwent carotid ultrasound and lacked a history of transient ischemic attack or stroke. The 5-year risks of 7 cerebrovascular disease outcomes used in ACAS were estimated for each cutoff. RESULTS: Associations with the 5-year risk of outcomes were substantially elevated only at cutoffs with high peak systolic velocities. In this population, the number of people with such high velocities was small. For example, with a cutoff of approximately 2.5 m/s, suggesting a stenosis of >70%, the 5-year risk of an ipsilateral fatal or nonfatal stroke was 5%, and only 0.5% of the group had velocities at least this high. CONCLUSIONS: In a group of older adults likely to participate in a screening program, as evidenced by willingness to participate in CHS, high peak systolic velocities consistent with high-grade carotid stenosis were uncommon and risk of subsequent cerebrovascular disease outcomes was relatively low. These findings do not suggest that similar populations of older adults would benefit from a program using ultrasound to screen for asymptomatic carotid stenosis.
Keywords: Aged; Blood Flow Velocity; Carotid Artery, Internal; Carotid Stenosis; Cerebrovascular Disorders; Cohort Studies; Female; Humans; Male; Prevalence; Risk Factors; Systole; Ultrasonography, Doppler

Hypoechoic plaque at US of the carotid artery: an independent risk factor for incident stroke in adults aged 65 years or older. Cardiovascular Health Study. - Polak, J F; Shemanski, L; O'Leary, D H; Lefkowitz, D; Price, T R; Savage, P J; Brant, W E; Reid, C (Radiology, 1998)
PURPOSE: To investigate the association between incident (first) stroke and the echogenicity of internal carotid arterial plaque at ultrasonography (US). MATERIALS AND METHODS: A cohort of 4, 886 individuals who, at baseline, were 65 years of age or older and without symptoms of cerebrovascular disease was followed up for an average of 3.3 years. Baseline clinical findings were from color Doppler and duplex US studies of the carotid arteries and a record of traditional risk factors: age, sex, presence of diabetes mellitus, pack-years of cigarette smoking, presence of hypertension, elevated systolic and diastolic blood pressure, elevated low-density lipoprotein cholesterol level. RESULTS: Incident strokes, excluding hemorrhagic strokes and strokes of cardiac origin, were seen in 104 individuals (2.1%) at risk. Age- and sex-adjusted odds ratios for incident stroke were significant for hypoechoic plaque (odds ratio, 2.53; 95% CI, 1,42,4.53). After controlling for risk factors in a Cox proportional hazards model, the relative risk (RR) of incident stroke was 1.72 (p = .015) for hypoechoic plaque and 2.32 (P = .004) for internal carotid arterial narrowing of at least 50%. In addition, hypoechoic plaque (RR, 2.78; CI, 1.36,5.69) and 50%-100% stenosis (RR, 3.08; CI, 1.28, 7.41) were associated with ipsilateral, nonfatal stroke. CONCLUSION: In asymptomatic adults aged 65 years or older, that risk of incident stroke was associated with two US features: hypoechoic internal carotid arterial plaque and an estimated internal carotid arterial stenosis of 50%-100%.
Keywords: Aged; Aged, 80 and over; Carotid Artery, Internal; Carotid Stenosis; Cerebrovascular Disorders; Cohort Studies; Female; Humans; Intracranial Arteriosclerosis; Male; Proportional Hazards Models; Risk; Ultrasonography, Doppler, Duplex; Ultrasonography, Doppler, Transcranial

Risk factors for 5-year mortality in older adults: the Cardiovascular Health Study. - Fried, L P; Kronmal, R A; Newman, A B; Bild, D E; Mittelmark, M B; Polak, J F; Robbins, J A; Gardin, J M (JAMA, 1998)
CONTEXT: Multiple factors contribute to mortality in older adults, but the extent to which subclinical disease and other factors contribute independently to mortality risk is not known. OBJECTIVE: To determine the disease, functional, and personal characteristics that jointly predict mortality in community-dwelling men and women aged 65 years or older. DESIGN: Prospective population-based cohort study with 5 years of follow-up and a validation cohort of African Americans with 4.25-year follow-up. SETTING: Four US communities. PARTICIPANTS: A total of 5201 and 685 men and women aged 65 years or older in the original and African American cohorts, respectively. MAIN OUTCOME MEASURES: Five-year mortality. RESULTS: In the main cohort, 646 deaths (12%) occurred within 5 years. Using Cox proportional hazards models, 20 characteristics (of 78 assessed) were each significantly (P<.05) and independently associated with mortality: increasing age, male sex, income less than $50000 per year, low weight, lack of moderate or vigorous exercise, smoking for more than 50 pack-years, high brachial (>169 mm Hg) and low tibial (< or = 127 mm Hg) systolic blood pressure, diuretic use by those without hypertension or congestive heart failure, elevated fasting glucose level (>7.2 mmol/L [130 mg/dL]), low albumin level (< or = 37 g/L), elevated creatinine level (> or = 106 micromol/L [1.2 mg/dL]), low forced vital capacity (< or = 2.06 mL), aortic stenosis (moderate or severe) and abnormal left ventricular ejection fraction (by echocardiography), major electrocardiographic abnormality, stenosis of internal carotid artery (by ultrasound), congestive heart failure, difficulty in any instrumental activity of daily living, and low cognitive function by Digit Symbol Substitution test score. Neither high-density lipoprotein cholesterol nor low-density lipoprotein cholesterol was associated with mortality. After adjustment for other factors, the association between age and mortality diminished, but the reduction in mortality with female sex persisted. Finally, the risk of mortality was validated in the second cohort; quintiles of risk ranged from 2% to 39% and 0% to 26% for the 2 cohorts. CONCLUSIONS: Objective measures of subclinical disease and disease severity were independent and joint predictors of 5-year mortality in older adults, along with male sex, relative poverty, physical activity, smoking, indicators of frailty, and disability. Except for history of congestive heart failure, objective, quantitative measures of disease were better predictors of mortality than was clinical history of disease.
Keywords: African Americans; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Female; Follow-Up Studies; Health Surveys; Humans; Male; Mortality; Proportional Hazards Models; Prospective Studies; Risk Factors; United States

Ankle-arm index as a predictor of cardiovascular disease and mortality in the Cardiovascular Health Study. The Cardiovascular Health Study Group. - Newman, A B; Shemanski, L; Manolio, T A; Cushman, M; Mittelmark, M; Polak, J F; Powe, N R; Siscovick, D (Arterioscler Thromb Vasc Biol, 1999)
Peripheral arterial disease (PAD) in the legs, measured noninvasively by the ankle-arm index (AAI) is associated with clinically manifest cardiovascular disease (CVD) and its risk factors. To determine risk of total mortality, coronary heart disease, or stroke mortality and incident versus recurrent CVD associated with a low AAI, we examined the relationship of the AAI to subsequent CVD events in 5888 older adults with and without CVD. The AAI was measured in 5888 participants >/=65 years old at the baseline examination of the Cardiovascular Health Study. All participants had a detailed assessment of prevalent CVD and were contacted every 6 months for total mortality and CVD events (including CVD mortality, fatal and nonfatal myocardial infarction, congestive heart failure, angina, stroke, and hospitalized PAD). The crude mortality rate at 6 years was highest (32.3%) in those participants with prevalent CVD and a low AAI (P<0.9), and it was lowest in those with neither of these findings (8.7%, P<0.01). Similar patterns emerged from analysis of recurrent CVD and incident CVD. The risk for incident congestive heart failure (relative risk [RR]=1.61) and for total mortality (RR=1.62) in those without CVD at baseline but with a low AAI remained significantly elevated after adjustment for cardiovascular risk factors. Hospitalized PAD events occurred months to years after the AAI was measured, with an adjusted RR of 5.55 (95% CI, 3.08 to 9.98) in those at risk for incident events. A statistically significant decline in survival was seen at each 0.1 decrement in the AAI. An AAI of <0.9 is an independent risk factor for incident CVD, recurrent CVD, and mortality in this group of older adults in the Cardiovascular Health Study.
Keywords: Age Distribution; Aged; Aged, 80 and over; Ankle; Arm; Blood Pressure Determination; Cardiovascular Diseases; Cohort Studies; Female; Humans; Hypertension; Male; Predictive Value of Tests; Risk Factors; Sex Distribution; Survival Analysis

Cardiovascular disease in older adults with glucose disorders: comparison of American Diabetes Association criteria for diabetes mellitus with WHO criteria. - Barzilay, J I; Spiekerman, C F; Wahl, P W; Kuller, L H; Cushman, M; Furberg, C D; Dobs, A; Polak, J F; Savage, P J (Lancet, 1999)
BACKGROUND: The new fasting American Diabetes Association (ADA) criteria for the diagnosis of diabetes mellitus rely mainly on fasting blood glucose concentrations and use a lower cut-off value for diagnosis than the WHO criteria. We aimed to assess the sensitivity of these criteria for the detection of cardiovascular disease, the main complication of diabetes mellitus in the elderly. METHODS: We did a cross-sectional and prospective analysis of 4515 participants of the Cardiovascular Health Study, an 8 year longitudinal study designed to identify factors related to the onset and course of cardiovascular disease in adults aged at least 65 years. We calculated the prevalence and incidence of cardiovascular disease for the ADA and WHO criteria. FINDINGS: There was a higher prevalence of cardiovascular disease among individuals with impaired glucose or newly diagnosed diabetes by both criteria than among those with normal glucose concentrations. However, because fewer individuals had abnormal glucose states by the fasting ADA criteria (22.3%) than by the WHO criteria (46.8%), the number of cases of cardiovascular disease attributable to abnormal glucose states was a third of that attributable by the WHO criteria (53 vs 159 cases per 10,000). For the two sets of criteria, the relative risk for incident cardiovascular disease (mean follow-up 5.9 years) was higher in individuals with impaired glucose and newly diagnosed diabetes than in those with normal glucose. Individuals classified as normal by the fasting ADA criteria had a higher absolute number of incident events (455 of 581 events) than those classified as normal by the WHO criteria (269 of 581 events). Fasting ADA criteria were therefore less sensitive than the WHO criteria for predicting cardiovascular disease among individuals with abnormal glucose (sensitivity, 28% vs 54%). INTERPRETATION: The new fasting ADA criteria seem to be less predictive than the WHO criteria for the burden of cardiovascular disease associated with abnormal glucose in the elderly.
Keywords: Age Factors; Aged; Blood Glucose; Cardiovascular Diseases; Cross-Sectional Studies; Diabetes Complications; Diabetes Mellitus; Fasting; Female; Glucose Intolerance; Humans; Longitudinal Studies; Male; Prospective Studies; Risk Factors; Sensitivity and Specificity; Societies, Medical; United States; World Health Organization

Carotid-artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults. Cardiovascular Health Study Collaborative Research Group. - O'Leary, D H; Polak, J F; Kronmal, R A; Manolio, T A; Burke, G L; Wolfson, S K (N Engl J Med, 1999)
BACKGROUND: The combined thickness of the intima and media of the carotid artery is associated with the prevalence of cardiovascular disease. We studied the associations between the thickness of the carotid-artery intima and media and the incidence of new myocardial infarction or stroke in persons without clinical cardiovascular disease. METHODS: Noninvasive measurements of the intima and media of the common and internal carotid artery were made with high-resolution ultrasonography in 5858 subjects 65 years of age or older. Cardiovascular events (new myocardial infarction or stroke) served as outcome variables in subjects without clinical cardiovascular disease (4476 subjects) over a median follow-up period of 6.2 years. RESULTS: The incidence of cardiovascular events correlated with measurements of carotid-artery intima-media thickness. The relative risk of myocardial infarction or stroke increased with intima-media thickness (P<0.001). The relative risk of myocardial infarction or stroke (adjusted for age and sex) for the quintile with the highest thickness as compared with the lowest quintile was 3.87 (95 percent confidence interval, 2.72 to 5.51). The association between cardiovascular events and intima-media thickness remained significant after adjustment for traditional risk factors, showing increasing risks for each quintile of combined intima-media thickness, from the second quintile (relative risk, 1.54; 95 percent confidence interval, 1.04 to 2.28), to the third (relative risk, 1.84; 95 percent confidence interval, 1.26 to 2.67), fourth (relative risk, 2.01; 95 percent confidence interval, 1.38 to 2.91), and fifth (relative risk, 3.15; 95 percent confidence interval, 2.19 to 4.52). The results of separate analyses of myocardial infarction and stroke paralleled those for the combined end point. CONCLUSIONS: Increases in the thickness of the intima and media of the carotid artery, as measured noninvasively by ultrasonography, are directly associated with an increased risk of myocardial infarction and stroke in older adults without a history of cardiovascular disease.
Keywords: Aged; Carotid Arteries; Cerebrovascular Disorders; Disease-Free Survival; Female; Humans; Incidence; Male; Myocardial Infarction; Proportional Hazards Models; Prospective Studies; Risk Factors; Tunica Intima; Tunica Media; Ultrasonography

Prevalence and associations of MRI-demonstrated brain infarcts in elderly subjects with a history of transient ischemic attack. The Cardiovascular Health Study. - Bhadelia, R A; Anderson, M; Polak, J F; Manolio, T A; Beauchamp, N; Knepper, L; O'Leary, D H (Stroke, 1999)
BACKGROUND AND PURPOSE: MRI is more sensitive than CT, but the significance of brain abnormalities seen on MR images obtained in older subjects with transient ischemic attack (TIA) is not clear. We studied the prevalence and risk factors associated with MRI-demonstrated infarcts in elderly subjects with a history of TIA. METHODS: Participants of the Cardiovascular Health Study, aged 65 years or more and without prior stroke, were studied with brain MRI (n=3456). The prevalence of brain infarcts (>/=3 mm) on MRI was determined in subjects with and without TIA. The cardiovascular risk factors and clinical and subclinical cardiovascular disease associated with MRI infarcts were studied in subjects with TIA. RESULTS: Subjects with TIA (n=100) had a higher prevalence of MRI infarcts than subjects without TIA (46% versus 28%; P<0.001). The unadjusted odds ratio for having MRI infarcts in subjects with TIA was 2.20 (95% CI, 1.47 to 3.30) and remained significantly elevated after adjustments for risk factors and cerebrovascular disease (odds ratio, 1.86; 95% CI, 1.23 to 2.83). In subjects with TIA, diastolic blood pressure (P=0.01) and internal carotid artery intima-media thickness (P=0.01) were the only factors predictive of the presence of MRI infarcts by stepwise logistic regression analysis. CONCLUSIONS: MRI infarcts are imaging manifestations of clinically important cerebrovascular disease in subjects with a history of TIA, given their increased prevalence and positive association with increased diastolic blood pressure and internal carotid artery intima-media thickness.
Keywords: Aged; Brain; Cardiovascular Diseases; Cerebral Infarction; Cross-Sectional Studies; Female; Humans; Ischemic Attack, Transient; Magnetic Resonance Imaging; Male; Odds Ratio; Population Surveillance; Predictive Value of Tests; Prevalence; Prospective Studies; Risk Factors; United States

Traditional risk factors and subclinical disease measures as predictors of first myocardial infarction in older adults: the Cardiovascular Health Study. - Psaty, B M; Furberg, C D; Kuller, L H; Bild, D E; Rautaharju, P M; Polak, J F; Bovill, E; Gottdiener, J S (Arch Intern Med, 1999)
BACKGROUND: Risk factors for myocardial infarction (MI) have not been well characterized in older adults, and in estimating risk, we sought to assess the individual and joint contributions made by both traditional risk factors and measures of subclinical disease. METHODS: In the Cardiovascular Health Study, we recruited 5888 adults aged 65 years and older from 4 US centers. At baseline in 1989-1990, participants underwent an extensive examination that included traditional risk factors such as blood pressure and fasting glucose level and measures of subclinical disease as assessed by electrocardiography, carotid ultrasonography, echocardiography, pulmonary function, and ankle-arm index. Participants were followed up with semiannual contacts, and all cardiovascular events were classified by the Morbidity and Mortality Committee. The main analytic technique was the Cox proportional hazards model. RESULTS: At baseline, 1967 men and 2979 women had no history of an MI. After follow-up for an average of 4.8 years, there were 302 coronary events, which included 263 patients with MI and 39 with definite fatal coronary disease. The incidence was higher in men (20.7 per 1000 person-years) than women (7.9 per 1000 person-years). In all subjects, the incidence was strongly associated with age, increasing from 7.8 per 1000 person-years in subjects aged 65 to 69 years to 25.6 per 1000 person-years in subjects aged 85 years and older. Glucose level and systolic blood pressure were associated with the incidence of MI, but smoking and lipid measures were not. After adjustment for age and sex, the significant subclinical disease predictors of MI were borderline or abnormal ejection fraction by echocardiography, high levels of intimal-medial thickness of the internal carotid artery, and a low ankle-arm index. Forced vital capacity and electrocardiographic left ventricular mass did not enter the stepwise model. Excluding subjects with clinical cardiovascular diseases such as prior angina or congestive heart failure at baseline had little effect on these results. Risk factors were generally similar in men and women. CONCLUSIONS: After follow-up of 4.8 years, systolic blood pressure, fasting glucose level, and selected subclinical disease measures were important predictors of the incidence of MI in older adults. Uncontrolled high blood pressure may explain about one quarter of the coronary events in this population.
Keywords: Age Distribution; Aged; Female; Follow-Up Studies; Humans; Incidence; Male; Multivariate Analysis; Myocardial Infarction; Predictive Value of Tests; Proportional Hazards Models; Risk; Risk Factors; Sex Distribution

Predictors of congestive heart failure in the elderly: the Cardiovascular Health Study. - Gottdiener, J S; Arnold, A M; Aurigemma, G P; Polak, J F; Tracy, R P; Kitzman, D W; Gardin, J M; Rutledge, J E; Boineau, R C (J Am Coll Cardiol, 2000)
OBJECTIVES: We sought to characterize the predictors of incident congestive heart failure (CHF), as determined by central adjudication, in a community-based elderly population. BACKGROUND: The elderly constitute a growing proportion of patients admitted to the hospital with CHF, and CHF is a leading source of morbidity and mortality in this group. Elderly patients differ from younger individuals diagnosed with CHF in terms of biologic characteristics. METHODS: We analyzed data from the Cardiovascular Health Study, a prospective population-based study of 5,888 elderly people >65 years old (average 73 +/- 5, range 65 to 100) at four locations. Multiple laboratory measures of cardiovascular structure and function, blood chemistries and functional assessments were obtained. RESULTS: During an average follow-up of 5.5 years (median 6.3), 597 participants developed incident CHF (rate 19.3/1,000 person-years). The incidence of CHF increased progressively across age groups and was greater in men than in women. On multivariate analysis, other independent predictors included prevalent coronary heart disease, stroke or transient ischemic attack at baseline, diabetes, systolic blood pressure (BP), forced expiratory volume 1 s, creatinine >1.4 mg/dl, C-reactive protein, ankle-arm index <0.9, atrial fibrillation, electrocardiographic (ECG) left ventricular (LV) mass, ECG ST-T segment abnormality, internal carotid artery wall thickness and decreased LV systolic function. Population-attributable risk, determined from predictors of risk and prevalence, was relatively high for prevalent coronary heart disease (13.1%), systolic BP > or =140 mm Hg (12.8%) and a high level of C-reactive protein (9.7%), but was low for subnormal LV function (4.1%) and atrial fibrillation (2.2%). CONCLUSIONS: The incidence of CHF is high in the elderly and is related mainly to age, gender, clinical and subclinical coronary heart disease, systolic BP and inflammation. Despite the high relative risk of subnormal systolic LV function and atrial fibrillation, the actual population risk of these for CHF is small because of their relatively low prevalence in community-dwelling elderly people.
Keywords: Aged; Aged, 80 and over; Coronary Disease; Female; Geriatric Assessment; Heart Failure; Humans; Ischemic Attack, Transient; Male; Prospective Studies; Risk Factors; Survival Rate

Association between physical activity and markers of inflammation in a healthy elderly population. - Geffken, D F; Cushman, M; Burke, G L; Polak, J F; Sakkinen, P A; Tracy, R P (Am J Epidemiol, 2001)
Higher levels of physical activity are associated with lower risk of cardiovascular disease. There is growing evidence that the development of the atherosclerotic plaque is associated with inflammation. In this study, the authors investigated the cross-sectional association between physical activity and markers of inflammation in a healthy elderly population. Data obtained in 1989-1990 and 1992-1993 from the Cardiovascular Health Study, a cohort of 5,888 men and women aged >/=65 years, were analyzed. Concentrations of the inflammation markers-C-reactive protein, fibrinogen, Factor VIII activity, white blood cells, and albumin-were compared cross-sectionally by quartile of self-reported physical activity. Compared with persons in the lowest quartile, those in the highest quartile of physical activity had 19%, 6%, 4%, and 3% lower concentrations of C-reactive protein, white blood cells, fibrinogen, and Factor VIII activity, respectively, after adjustment for gender, the presence of cardiovascular disease, age, race, smoking, body mass index, diabetes, and hypertension. Multivariate regression models suggested that the association of higher levels of physical activity with lower levels of inflammation markers may be mediated by body mass index and glucose. There was no association between physical activity and albumin. Higher levels of physical activity were associated with lower concentrations of four out of five inflammation markers in this elderly cohort. These data suggest that increased exercise is associated with reduced inflammation. Prospective studies will be required for verification of these findings.
Keywords: Aged; Analysis of Variance; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Factor VIII; Female; Fibrinogen; Humans; Inflammation; Leukocyte Count; Male; Physical Exertion; Sex Factors; Smoking

Risk factors for hospitalized gastrointestinal bleeding among older persons. Cardiovascular Health Study Investigators. - Kaplan, R C; Heckbert, S R; Koepsell, T D; Furberg, C D; Polak, J F; Schoen, R E; Psaty, B M (J Am Geriatr Soc, 2001)
OBJECTIVES: We sought to estimate the incidence of hospitalization for upper and lower gastrointestinal bleeding among older persons and to identify independent risk factors. DESIGN: Prospective cohort study. SETTING: The Cardiovascular Health Study (CHS). PARTICIPANTS: 5,888 noninstitutionalized men and women age 65 years or older in four U.S. communities enrolled in the CHS. MEASUREMENTS: Gastrointestinal bleeding events during the period 1989 through 1998 were identified using hospital discharge diagnosis codes and confirmed by medical records review. Risk-factor information was collected in a standardized fashion at study baseline and annually during follow-up. RESULTS: Among CHS participants (mean baseline age 73.3 years, 42% male), the incidence of hospitalized gastrointestinal bleeding was 6.8/1,000 person-years. In multivariate analyses, advanced age, male sex, unmarried status, cardiovascular disease, difficulty with daily activities, use of multiple medications, and use of oral anticoagulants were independent risk factors. Compared with nonsmokers, subjects who smoked more than half a pack per day had a multivariate-adjusted hazard ratio (HR) of 2.14 (95% confidence interval [CI] = 1.22-3.75) for upper gastrointestinal bleeding and a multivariate-adjusted HR of 0.21 (95% CI = 0.03-1.54) for lower gastrointestinal bleeding. Aspirin users did not have an elevated risk of upper gastrointestinal bleeding (HR = 0.76, 95% CI = 0.52-1.11), and users of other nonsteroidal anti-inflammatory drugs had a HR of 1.54 (95 % CI = 0.99-2.36). Low ankle-arm systolic blood pressure index was associated with higher risk of gastrointestinal bleeding among subjects with clinical cardiovascular disease but not among those without clinical cardiovascular disease. CONCLUSION: This study identifies risk factors for gastrointestinal bleeding, such as disability, that may be amenable to modification. The findings will help clinicians to identify older persons who are at high risk for gastrointestinal bleeding.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Anti-Inflammatory Agents, Non-Steroidal; Anticoagulants; Aspirin; Cardiovascular Diseases; Female; Gastrointestinal Hemorrhage; Hospitalization; Humans; Incidence; Male; Multivariate Analysis; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; Smoking; United States

The role of comorbidity in the assessment of intermittent claudication in older adults. - Newman, A B; Naydeck, B L; Sutton-Tyrrell, K; Polak, J F; Kuller, L H (J Clin Epidemiol, 2001)
The prevalence of intermittent claudication (IC) in older adults by questionnaire is less than 5% while the prevalence of peripheral arterial disease (PAD) by non-invasive testing is 2-4-fold higher. Comorbid conditions may result in under-reporting intermittent claudication (IC) as assessed by the Rose Questionnaire. We examined characteristics of those who report leg pain in relationship to other comorbid conditions and disability in 5888 participants of the Cardiovascular Health Study (CHS). Older adults with exertional leg pain, not meeting criteria for IC, had a higher prevalence of PAD on non-invasive testing with the ankle-arm index than those without pain, as well as a higher prevalence of arthritis. The pattern of responses suggested that pain for both conditions was reported together. The Rose Questionnaire for IC is specific for PAD, but a negative questionnaire does not indicate a lack of symptoms, rather the presence of PAD along with other conditions that can cause pain.
Keywords: Aged; Angina Pectoris; Arterial Occlusive Diseases; Cerebrovascular Disorders; Cohort Studies; Comorbidity; Diabetes Mellitus; Female; Humans; Intermittent Claudication; Leg; Male; Prevalence; Sensitivity and Specificity; Surveys and Questionnaires